(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Profitability is a crucial indicator in assessing the performance of Rural Banks (BPR). However, in recent years, BPRs in DKI Jakarta have faced a decline in profitability, as evidenced by a negative average profitability level. Furthermore, previous research on the effect of liquidity on profitability has yielded inconsistent findings. Therefore, this study aims to analyze the effect of liquidity on BPR profitability in DKI Jakarta. The study employed a quantitative approach using the Ordinary Least Square (OLS) method. The data used were annual financial data from all 31 BPRs operating in DKI Jakarta during the 2020–2025 period. The analysis was conducted using six research models and robustness tests, incorporating control variables to verify consistency. The results showed that liquidity did not significantly impact profitability across all estimated models. This finding indicates that BPR profitability in DKI Jakarta is not determined solely by liquidity but rather by factors beyond the research model. This study implies that BPR profitability management needs to consider internal and external factors in addition to liquidity.